The Role of Kinesiotaping Combined With Botulinum Toxin to Reduce Plantar Flexors Spasticity After Stroke - KARADAĞ SAYGI, NAİME EVRİM (THOMAS LAND PUBLISHERS, INC, 2010)
Purpose: To evaluate the effect of kinesiotaping as an adjuvant therapy to botulinum toxin A (BTX-A) injection in lower extremity spasticity. Methods: This is a single-center, randomized, and double-blind study. Twenty hemiplegic patients with spastic equinus foot were enrolled into the study and randomized into 2 groups. The first group (n=10) received BTX-A injection and kinesiotaping, and the second group (n=10) received BTX-A injection and sham-taping. Clinical assessment was done before injection and at 2 weeks and 1, 3, and 6 months. Outcome measures were modified Ashworth scale (MAS), passive ankle dorsiflexion, gait velocity, and step length. Results: Improvement was recorded in both kinesiotaping and sham groups for all outcome variables. No significant difference was found between groups other than passive range of motion (ROM), which was found to have increased more in the kinesiotaping group at 2 weeks. Conclusion: There is no clear benefit in adjuvant kinesiotaping application with botulinum toxin for correction of spastic equinus in stroke.
Keywords: botulinum toxin A; hemiplegia; kinesiotaping; spasticity; ELECTRICAL-STIMULATION; HEMIPARETIC PATIENTS; DROP FOOT; ANKLE; INJECTION